2004
DOI: 10.1037/0090-5550.49.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Children With Sickle Cell Disease: Family Functioning and Coping.

Abstract: to determine the effects of coping style and family functioning on children's adjustment to sickle cell disease (SCD). Participants: A sample of 73 caregivers and 23 children (ages birth to 18 years) admitted to a hematology acute care unit for pain or fever associated with SCD. Setting: A children's hospital on the East Coast of the United States. Outcome Measures: Disability stress, disease severity, child and parent coping, family functioning, and child adjustment were assessed with standard paper-and-penci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These findings are similar to past studies, in that hypothesized mediator and moderator models with hope [28] and coping [29] were not supported. However, there were a number of important factors highlighted within the models indicating that pathways to resiliency may be more complex.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are similar to past studies, in that hypothesized mediator and moderator models with hope [28] and coping [29] were not supported. However, there were a number of important factors highlighted within the models indicating that pathways to resiliency may be more complex.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have failed to find a relation between disease variables, such as SCD-related emergency room visits or pain frequency and intensity, and psychosocial adjustment (Burlew et al, 2000;Casey et al, 2000;Hurtig et al, 1989;Lutz et al, 2004;Noll et al, 1996). These findings highlight the potential influence of psychosocial factors on adjustment.…”
Section: Medical Explanations For Child Adjustmentmentioning
confidence: 67%
“…The authors of the study concluded that the disease affects males more significantly in adolescence, possibly because SCD's impact on physical growth and physical activities is more likely to affect peer interactions. A more recent study found that girls with SCD self-reported a better quality of life than boys with SCD (Lutz et al, 2004). The boys in the sample had more SCD-related visits to the emergency room, more pain episodes and more contacts with health care professionals.…”
Section: Child Adjustment To Scdmentioning
confidence: 96%
See 1 more Smart Citation
“…About this issue, our review suggests that the effectiveness of children interventions could be improved if we involve parents in the process, something which there is little consensus about. Some researchers argue that parents care would be sufficient to improve the children's adjustment (Hastings & Beck, 2004), while others seem to be favorable to a joint intervention (Barakat, Lutz, Nicolaou & Lash, 2005;Fuemmeler et al, 2003;Klassen et al, 2011, Landolt, Vollrath, Niggli, Gnehm & Sennhauser., 2006 and a third group claims that there is no relationship between improvement of children and parents (Grootenhuis & Last, 1997;Lutz, Barakat, Smith-Whitley & Ohene-Frempong, 2004;Robinson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%